PENGARUH CITRA TOKO DAN KEPERCAYAAN TERHADAP KEPUTUSANPEMBELIAN ONLINE PADA NDY SHOP - MADE SHITA K W, NI (Jurnal Ilmu Manajemen (JIM), 2013)
Technology developments are progressing very rapidly has created a new step in making spending to meet demand. Sales can occur from and to anywhere and anytime regardless of working hours. It is not independent of the behavior patterns that tend as if the dependence on the Internet, because the Internet as source of information in many ways. It is Ndy Shop. This study to examine the effect of store image and trust in online purchasing decisions either partially or simultaneously. Judgmental sampling method of sampling used by the consumer of Ndy Shop as the population, so the number of samples obtained by 110 consumer. The method of data analysis using multiple linear regression with SPSS. The results of the analysis in this study showed that there is significant influence between variable store image and trust in online purchasing decisions either partially or simultaneously. Keywords: store image, trust, and purchase decisions.